2013
DOI: 10.3238/arztebl.2013.0413
|View full text |Cite
|
Sign up to set email alerts
|

Health in the Long-Term Unemployed

Abstract: SUMMARYBackground: Although the unemployment rate in Germany is currently low, more than a million persons in the country have been out of work for more than a year. In this review article, we address these persons' state of health, the effect of unemployment on health, and the influence of macroeconomic factors and social policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
87
1
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 38 publications
4
87
1
17
Order By: Relevance
“…No reciprocal associations of NEET status with substance use appeared, as reported in studies focusing separately on unemployment and school disengagement [6].…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…No reciprocal associations of NEET status with substance use appeared, as reported in studies focusing separately on unemployment and school disengagement [6].…”
Section: Discussionmentioning
confidence: 62%
“…The prospective pathways from NEET status to mental health showed that youth with prior mental health issues were more likely to become NEET [5,6]. Indeed, having mental health increased the risk of becoming an NEET.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So ist vielfach dokumentiert, dass insbesondere psychische Erkrankungen, wie z. B. Depressionen und Angststörungen, bei Arbeitslosen vermehrt auftreten [1,7,17]. Die "Selektionsthese" geht davon aus, dass Erwerbstätige mit chronischen Gesundheitsproblemen ein höheres Arbeitslosigkeitsrisiko sowie schlechtere Chancen auf eine Wiederbeschäftigung haben [5,[18][19][20].…”
unclassified